1984
DOI: 10.2118/10928-pa
|View full text |Cite
|
Sign up to set email alerts
|

Light-Oil Steamflooding An Emerging Technology

Abstract: Summary This paper discusses the extension of the steamflood process to the recovery of light oil and the state of the art of this emerging technology. A review of the various steamflood mechanisms indicates that distillation will dominate if steam is injected into light-oil reservoirs. The results of light-oil steamflood laboratory studies, computer simulations, and field projects are also reviewed. A rough screening guide for selecting a light- projects are also reviewed. A rough screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 0 publications
3
17
0
Order By: Relevance
“…Thus, the predicted oil gravity slightly increases from 25 to 27°API. All these results are consistent with the physical simulations experiments and with previous reports in the literature 4,[8][9][10][11][12] .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the predicted oil gravity slightly increases from 25 to 27°API. All these results are consistent with the physical simulations experiments and with previous reports in the literature 4,[8][9][10][11][12] .…”
Section: Resultssupporting
confidence: 93%
“…These later results are attributed to a steam distillation mechanism, which "boils off" the lighter components with the concomitant increase in the percentage of oil recovery with respect to hot water displacement, as mentioned in the Introduction. Similar results have been proposed by other authors in their physical and numerical simulation studies [8][9][11][12][13][14][15] .…”
Section: Resultssupporting
confidence: 90%
“…Light-oil reservoirs have had fewer steamflood applications even where depth and other factors are favorable because of the generally lower post-secondary oil in place. 1,2 Unlike heavy-oil steamflood projects, there are no large-scale commercial light-oil projects to use as analogs for design purposes. There are, however, a number of field trials in the literature, which have been reported both as successes and as failures.…”
Section: Introductionmentioning
confidence: 99%
“…15 The overall screening criteria for the light-oil steamflood are shown in Table 4. 1 All the above reservoirs met these screening criteria. Although these criteria are useful preliminary guidelines, the failed projects show that each reservoir should be examined individually.…”
Section: Introductionmentioning
confidence: 99%
“…The difference lies in the amount a particular mechanism effects a particular hydrocarbon reservoir (Blevins, et al, 1984) . Figure 2 qualitatively displays the roles certain mechanisms play for light to heavy oils.…”
Section: Mechanismsmentioning
confidence: 99%